HUBUNGAN HARGA DIRI DAN PENGETAHUAN TENTANG BULLYING DENGAN PERILAKU BULLYING PADA REMAJA - Anissa Duwi Nur A’ini, Andriati Reny H (JURNAL ILMIAH KEPERAWATAN ALTRUISTIK)
Bullying behavior is a desire to hurt both physically, psychologically or verbally, which causes a person to suffer. One of the factors that causes a teen to do bullying is self-esteem and knowledge. The purpose of this research is to determine the relationship between self-esteem and knowledge about bullying with bullying behavior on adolescents. The population of the research is was the class X and XI as many as 1093 respondents, with a total sample of 190 respondents in the SMK Insan Kreatif Cibinong-Bogor with the sampling technique used was stratified random sampling. The results of the research using the chi-square test with a confidence level of 95% (p-value = 0.05). The results of this study indicate that there is a significant relationship between self-esteem and bullying behavior in adolescents with p-value = 0,000 and there is a relationship between knowledge about bullying and bullying behavior in adolescents with p-value = 0.002.   Keyword   : Bullying, self-esteem, Knowledge.